EFL NOVICE TEACHERS’ EMOTION REGULATION IN INDONESIAN PRIMARY AND SECONDARY SCHOOLS: EMOTIONAL LABOR - Gloria Gloria; Concilianus Laos Mbato (PROJECT (Professional Journal of English Education), 2024)
Teachers’ emotions can impact the classroom’s learning atmosphere and affect students’ motivation and engagement. By involving emotional labor, teachers can pursue their professional goals, such as teaching effectively and maintaining a positive relationship with students and colleagues. This study explored the emotional labor of EFL novice teachers at different levels of schools using the Critical Incident Technique (CIT) to collect data and establish triangulation using an open-ended FGD questionnaire and in-depth interviews. Six EFL novice teachers in Indonesian primary and secondary schools were purposefully chosen as the participants of this study. Thematic analysis was employed to code and organize the themes when assessing the data. The findings showed that EFL beginner teachers used various emotional labor strategies depending on their teaching experiences, the nature of interactions, and their relationships with students, parents, and colleagues. Surface acting was visible when teachers needed to hide their negative emotions while displaying positive ones. Still, deep acting was more prominent when teachers demonstrated empathy and sincerity in their interactions. Therefore, understanding emotional labor strategies will enable novice teachers to improve their well-being and effectiveness in the classroom. The study suggested future research on EFL teachers’ emotional experiences, emphasizing the need for a deeper understanding of both experienced and novice teachers’ emotional labor.